Aggregate loans to the euro area private sector - Alessandro Calza; Marta Manrique; Jo\~ao Sousa (European Central Bank (ECB), 2003)
This paper provides new evidence on the behaviour of euro area aggregate loans to the private sector. Using a sample covering the last twenty years, a cointegrating vector linking the real stock of loans to a small set of domestic macroeconomic variables is found. Besides real GDP and prices, this set includes a new measure of the cost of loans obtained as a weighted average of bank lending rates. The results are overall encouraging, though the recursive estimates of the long-run parameters suggest that in 2000 some disturbances, probably of a temporary nature, affected the system. The study then addresses the issue of the leading indicator properties of loans. It finds that the deviations of the real stock of loans from the equilibrium level implied by the model seem to contain information on future changes in inflation, though not on its level.
Keywords: C32; C51; 330; cointegration; credit; euro area; loans